Diagnostic accuracy of 68Ga‐prostate‐specific membrane antigen (PSMA) positron‐emission tomography (PET) and multiparametric (mp)MRI to detect intermediate‐grade intra‐prostatic prostate cancer using whole‐mount pathology: impact of the addition of 68Ga‐PSMA PET to mpMRI. (9th July 2019) - Scheltema, Matthijs J.; Chang, John I.; Stricker, Phillip D.; van Leeuwen, Pim J.; Nguyen, Quoc A.; Ho, Bao; Delprado, Warick; Lee, Jonathan; Thompson, James E.; Cusick, Thomas; Spriensma, Alette S.; Siriwardana, Amila R.; et al.
Abstract : Objective: To evaluate the ability of prostate‐specific membrane antigen (PSMA)‐positron‐emission tomography (PET)/computed tomography (CT) to detect intermediate‐grade intra‐prostatic prostate cancer (PCa), and to determine if PSMA‐PET improves the diagnostic accuracy of multiparametric magnetic resonance imaging (mpMRI). Patients and Methods: A total of 56 consecutive patients with International Society of Urological Pathology (ISUP) grade 2–3 PCa after radical prostatectomy, who underwent both mpMRI and PSMA‐PET CT (hereafter PSMA‐PET) preoperatively, were enrolled in this study. The accuracy of PSMA‐PET, mpMRI alone, and the two procedures in combination was analysed for identifying ISUP grades 1–3 within a 12‐segment model. The accuracy of a combined predictive model (PSMA‐PET and mpMRI) was determined. Receiver‐operating characteristic curve analysis to determine the optimal standardized uptake value (SUVmax ) for PSMA‐PET in discriminating between ISUP grades 1 and ≥2 was performed. Results: On a per‐patient basis, the sensitivities for PSMA‐PET and mpMRI in identifying ISUP grades 2–3 PCa were 100% and 97%, respectively. Assessing ISUP grade ≥2 PCa using a 12‐segment analysis, PSMA‐PET demonstrated greater diagnostic accuracy (area under the curve), sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV), with values of 0.91, 88%, 93%, 95% and 85%, respectively, than did mpMRI (Prostate Imaging Reporting and Data System [PI‐RADS] 3–5), at 0.79, 68%, 91%, 87%, and 75%, respectively. When used in combination (PSMA‐PET and mpMRI PIRADS 4–5), sensitivity, specificity, NPV and PPV were 92%, 90%, 96% and 81%, respectively. The sensitivity for both techniques reduced markedly when assessing ISUP grade 1 PCa (18% for PSMA‐PET, 10% for mpMRI). An SUVmax value of 3.95 resulted in 94% sensitivity and 100% specificity. Conclusion: PSMA‐PET is accurate in detecting segments containing intermediate‐grade intra‐prostatic PCa (ISUP grade ≥ 2), compared with and complementary to mpMRI. By contrast the detection rate for ISUP grade 1 disease for both PSMA‐PET and mpMRI was low.